Animals, Quo Vadis? Welcome to a New, Multidisciplinary, Integrated, Open Access Journal: Animals - Clive Phillips (Animals, 2010)
Without animals this planet would be a very different place, indeed many of the remaining life forms could not exist. As animals ourselves we are linked to a vast network of moving, living, reproducing organisms that form an essential part of the various ecosystems that are themselves competing for survival. By virtue of our large cognitive capacity and complex societal living structures, we manage and influence many of these ecosystems, in the most extreme way by keeping animals captive for our own benefit. [...]